2006
DOI: 10.1071/wf06009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of forest fires in Canada, 1980 - 1999

Abstract: The present study characterized the spatial patterns of forest fires in 10 fire-dominated ecozones of Canada by using a database of mapped fires ≥200 ha from 1980 to 1999 (n = 5533 fires). Spatial metrics were used individually to compare measures of fire size, shape (eccentricity and complexity), clustering, and geographic orientation among ecozones and were used concurrently in a multivariate analysis. In addition, a set of factors that influence the fire regime at the ecozone level – topography, climate, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 42 publications
6
59
0
2
Order By: Relevance
“…Además, ellos sugieren que estos patrones son propensos a responder de manera diferente a los cambios en la escala espacial. De hecho, Parisien et al (2006) muestran que la división de los grupos, y por lo tanto la reducción de las unidades de estudio, evitaría un sesgo en las estimaciones y seguramente diluye el efecto de la agrupación. Bajo este enfoque, la elección de los sistemas terrestres como unidades de estudio en este trabajo, no es totalmente arbitraria, ya que se basa en las unidades para las cuales se conoce la actividad del fuego y su variación a lo largo de la zona de estudio.…”
Section: Discussionunclassified
“…Además, ellos sugieren que estos patrones son propensos a responder de manera diferente a los cambios en la escala espacial. De hecho, Parisien et al (2006) muestran que la división de los grupos, y por lo tanto la reducción de las unidades de estudio, evitaría un sesgo en las estimaciones y seguramente diluye el efecto de la agrupación. Bajo este enfoque, la elección de los sistemas terrestres como unidades de estudio en este trabajo, no es totalmente arbitraria, ya que se basa en las unidades para las cuales se conoce la actividad del fuego y su variación a lo largo de la zona de estudio.…”
Section: Discussionunclassified
“…Within natural vegetation, there are 16 plant functional types (PFTs), four of which occur in boreal/arctic North America, and bare ground. We defined our domain on this grid to be North American grid cells that contained at least 50 % boreal/arctic vegetation cover within the vegetated fraction, at least 1 % tree cover from MODIS, and at least one fire within the Alaska Large Fire Database (Kasischke et al, 2002) or the Canadian National Fire Database (Amiro et al, 2001;Stocks et al, 2003;Parisien et al, 2006) (NFDBs) (Fig. 1).…”
Section: Boreal Forest Domainmentioning
confidence: 99%
“…However, landscape metrics have also begun to be reported for burned area products [24], and patch scale metrics, such as fire size distribution, have been calculated for global burned area products [41,42]. A number of studies have shown that measurements informing the spatial pattern of fires can both complement our understanding of fire regimes [8,43,44] and inform post-fire dynamics [45][46][47]. At broad spatial and temporal scales, the patterns and abundance of fires are controlled by continental-scale variation in climate and long-term patterns in vegetation type and successional stage [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…However, at finer spatial and temporal scales, spatial heterogeneity in fire occurrence, extent or severity can be attributed to variation in fuels, ignition sources, topography, weather, and barriers to fire spread [44,51,52]. For example, fire orientation has been successfully related to locally dominant wind directions, which can inform efforts to place fuel breaks on the landscape [8,53,54]. An understanding of the controls on burned area extent across space and time is critical to anticipating shifts in fire regimes under climate change [55].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation